Validation of a self-report questionnaire addressing antisocial behavior in adolescents: CACSA - Bañares, Paula Alarcón; Pérez-Luco, Ricardo; Salvo, Sonia; Roa, Gloria; Jaramillo, Katherine; Sanhueza, Carla (Paidéia (Ribeirão Preto), 2010)
This paper reports the validation of a rationally built self-report instrument to assess social behavior in Chilean adolescents (CACSA) and presents the findings on social behavior from two samples: school attending adolescents (N=1914) and juvenile offenders (N=264). The questionnaire consists of 56 items, which explore three general behavioral dimensions: Prosocial (CPRO) and Antisocial (CAT) behavior, and Victims of Abuse of Power (VAP); CAT contains six specific dimensions: Crimes (D), Transgressions Against Property (TPRO), Transgressions Against Persons (TPER); Abusive Behavior with Peers (CAP), Substance Abuse (OHD); and Minor Social Transgressions (TSL). The study also includes a social desirability scale and an attitudinal scale. Results revealed the questionnaire has important psychometric strengths, as well as discriminative properties between the school attending adolescents and the juvenile offenders. The importance and reliability of self-report data for building indices of antisocial behavior is discussed, as well as the relationship between prosocial and antisocial behavior among Chilean adolescents.